1992
DOI: 10.1182/blood.v79.8.2131.2131
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the polymorphonuclear neutrophil Fc gamma receptor III deficiency in the French population and its involvement in the development of neonatal alloimmune neutropenia

Abstract: We report the case of a healthy woman (K.M.) who, after multiple pregnancies, developed an antibody directed against a nonpolymorphic region of the polymorphonuclear neutrophil (PMN) Fc gamma receptor III (FcRIII-CD16), which caused transient neonatal alloimmune neutropenia (NAIN). The antigenic target of the antibody was determined by an immunoprecipitation procedure and by phenotyping the mother's PMN. These latter did not react with monoclonal CD16 or polyclonal and monoclonal NA1 and NA2 antibodies, demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
2
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 21 publications
3
44
2
2
Order By: Relevance
“…A French group found 4 (0.1%) HNA‐1 null among 3377 tested subjects, whereas a study from Spain reported 4 HNA‐1 null individuals among 500 tested. In Brazil, our group found 11 of 92 Amazon native Indians who could represent deletions of NA 1 and NA 2 genes (13, 15, 16). In the present study, we did not identify NA‐null phenotype in Brazilian individuals probably because of the relative small number of tested subjects ( n = 100).…”
Section: Discussioncontrasting
confidence: 73%
“…A French group found 4 (0.1%) HNA‐1 null among 3377 tested subjects, whereas a study from Spain reported 4 HNA‐1 null individuals among 500 tested. In Brazil, our group found 11 of 92 Amazon native Indians who could represent deletions of NA 1 and NA 2 genes (13, 15, 16). In the present study, we did not identify NA‐null phenotype in Brazilian individuals probably because of the relative small number of tested subjects ( n = 100).…”
Section: Discussioncontrasting
confidence: 73%
“…In addition, we found 11 Amerindians (12.0%) whose DNA samples were not amplified for NA1 or NA2 alleles. Several persons have been described in the literature whose neutrophils lack the low‐affinity FcγRIIIB and who were therefore classified as “NA null.” A French group found 4 “NA null” cases among 3377 tested, 11 a study from Spain reported 4 “NA null” individuals among 500 tested, 12 and a German investigation found 1 “NA null” subject among more than 1000 tested blood donors 13 . On the other hand, variations in NA1 and NA2 alleles have recently been described, but, when analyzed by flow cytometry with specific antibodies, the neutrophils from subjects with such genetic variations do not show phenotypic changes 14 .…”
Section: Discussionmentioning
confidence: 97%
“…The third allele product, SH (HNA‐1c), differs from NA2 by a single amino acid substitution, and is present in a small proportion of Caucasians as well as in a larger proportion of the African population (11). Furthermore, approximately 0.1% of the European population was shown to be deficient in the FCGR3B gene (16).…”
mentioning
confidence: 99%